ANALISIS MAKNA PANTUN PADA LIRIK LAGU “SELAYANG PANDANG” KARYA LILY SUHAIRY DAN HAMIEDHAN AC - Siti Rosidah; Asep Barhoya; Rosi Rosi (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This study aims to describe: (1) the rhymes contained in the lyrics of the song at a glance the work of Lily Suhairy and Hamiedhan A.C, (2) the meaning of pantun contained in the lyrics of the song at a glance the work of Lily Suhairy and Hamiedhan A.C. This research is qualitative descriptive form, this research use technique of analysis with technique of collecting data using literature research technique. The data analysis technique begins with reading all the lyrics of the song to be analyzed, then searching for the elements of pantun and the meaning of the rhyme that is in the lyrics of the song at a glance the works of Lily Suhairy and Hamiedhan A.C. Sources of data used are documents and informants. The purpose of this study is to know the elements of pantun and the meaning of pantun contained in the lyrics of the song at a glance the work of Lily Suhairy and Hamiedhan A.C. The conclusion of this research is that there are elements of pantun contained in the lyrics of the song at a glance the work of meaningful admiration of love and motivation.